Integrated Management Systems in Industry 4.0: Literature Review - Pinto, Cátia; Domingues, Pedro; Sampaio, Paulo; Oliveira, Otávio [UNESP] (My University, 2022)
Purpose: Management Systems (MS) are a global phenomenon, and their integration is justified by the benefits that they provide to organizations. Thus, the main purpose of this paper was based on the analysis of the existing literature, with a view to characterizing the current state of the art to understand the impact that Industry 4.0 (I4.0) will have on Integrated Management Systems (IMS). Design/methodology/approach: For this study, exploratory bibliographic research was carried out to extract the most important ideas from the literature, to better understand the main concepts related to ISO 9001, ISO 14001, and ISO 45001, considering the fourth industrial revolution. The methodological basis used in this study followed the PRISMA guidelines and the research was carried out essentially through two databases, Scopus, and Web of Science. Findings: The integration of MS will be one of the pillars of I4.0 and it aims to interconnect the different areas of an industry, whose objective is to extract data and information that will be used to carry out continuous improvements in the entire production process and in all the related support areas. This paper reviews, lists and organizes the different technological concepts and integration opportunities that have been explored within the scope of IMS in I4.0. Research limitations/implications: Although this literature review is limited to the aforementioned databases, there is still not much information available regarding the focus of IMS in I4.0. Originally/value: This study contributed to a better perception and systematization of the IMS considering the I4.0. It focuses on the motivation and importance of ISO certifications, related to quality (9001), environment (14001) and occupational health and safety (45001) in I4.0. Thus, the contribution of this work aimed essentially to provide information about possible benefits and difficulties that may occur due to the implementation of IMS in I4.0 context.
Keywords: Industry 4.0; Integrated Management Systems; ISO 14001; ISO 45001; ISO 9001